Literature study of accounting research management organizational accounting - Diana Putri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to reveal the development of research in accounting management science sourced from the journal Management Accounting Research volume 50-53. There are 16 articles that are used as analytical materials out of three volumes in 2021. The stages of analysis carried out include analyzing the literature used for research, archival documents that support research, collecting cases related to research, experimentation from several cases from research, field studies, making a framework from field studies, reviews resulting from findings, surveys for confirm the findings, and simulate for the final results. Based on these stages, this article focuses on the topic of accounting management which consists of (1) honesty in budget reporting; (2) the role of organizational culture and information systems in management strategy; (3) controlling the sustainability of the organization's activities; and (4) economic policy uncertainty and cost rigidity.This research is only limited to the study of existing biographies in one journal, without any comparisons from other journals so that it has not been able to form a new pattern in the development of management accounting studies. For this reason, the results of this biography study cannot be generalized to assess the development of studies on management accounting